Voriconazole-induced periostitis - D.C. Fernández Ávila; M. Diehl; A.M. Degrave; M. Buttazzoni; T. Pereira; M.A. Aguirre; A.L. Basquiera; M. Scolnik (PAGEPress Publications, 2021)
Voriconazole is a fluorinated drug from the triazole group that is widely used in the prophylaxis and treatment of fungal infections in immunosuppressed patients. Chronic use of this medication can generate, as an adverse effect, a multifocal, asymmetric, diffuse and nodular periosteal reaction, associated with severe and disabling skeletal pain and elevated alkaline phosphatase and serum fluoride. Radiography is the imaging technique of choice for periostitis diagnosis. In general, clinical manifestations and radiographic findings disappear, when the drug is discontinued. We report the clinical case of a 44 year-old woman diagnosed with acute myeloid leukemia, who developed an invasive fungal infection treated with voriconazole after a stem cell transplant. Nine months after starting antifungal treatment, she manifested symptoms and radiological signs compatible with periostitis. Due to clinical suspicion, we decided to suspend voriconazole, with consequent resolution of clinical manifestations and radiological findings.